Interpretative structural modeling for implementing the pelagic fish habitat suitability model in Palabuhanratu Bay and Its surroundings, West Java, Indonesia - Gilar Budi Pratama; Prihatin Ika Wahyuningrum; Mustaruddin Mustaruddin; Yeni Herdiyeni; Ronny Irawan Wahju; Tri Wiji Nurani (Fisheries and Aquatic Sciences)
A habitat suitability model for pelagic fish in Palabuhanratu Bay and its surroundings was developed to enhance the efficiency and effectiveness of fishing activities. Interpretative structural modelling was used to implement the model with input from six expert respondents. The study identified the key elements for the successful implementation of the model, particularly within the activity sub-elements. These including conducting training on information systems and improving fishers’ ability to interpret fishing ground maps. The key elements in the constraint sub-elements were the limited ability of fishers to interpret fishing ground maps, the lack of oceanographic information provided by fishing ports, and the high dependence of fishers on the presence of fish-aggregating devices in pelagic fishing. The key elements in the activity sub-elements that should be carried out are in-depth involvement and coordination among The Marine Fisheries Agency of the Sukabumi Regency, Palabuhanratu fishing port, and local fisher groups.